ANALISIS KINERJA REKSADANA SAHAM DENGAN METODA SHARPE DAN TREYNOR PERIODE DESEMBER 2006 â DESEMBER 2011 - , Lukiani Nainggolan ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mutual Fund can be used as an alternative investment amongst savings accounts, time deposits, stocks and bonds. Mutual fund is an investment that has a form as a collective contract investment and managed by the professionals. There is a various choice of mutual funds in the market therefore investorsshouldcarefullychoose mutualfundsthat can provide the optimalReturn. This study aims toanalyze the performance ofequity fundstoprovide an overviewfor investorswhowant to investinmutual funds. The writer conducted a study of 24 equity funds that exist in Indonesia for the period December 31, 2006 until December 31, 2011. First, the writer calculates all mutual funds according to their performance based on Sharpe and Treynor method. Mutual fund that outperforms market performance considered as superior mutual fund, and then to find out whether there is any consistency in the performance of mutual funds will be conducted by probability method which shows the consistency of 54.69%. Then ranking will be made started from the best to the worst mutual fund. The best mutual fund is a mutual fund that seeded at least three times superior position over five years of the research period based on Sharpe methods and Treynor methods. The best mutual funds are mutual fund that obtains the highest rank according to the two methods. The following rank is the rank of equity-based mutual funds with superior performance: Panin Dana Maksima, BNP Paribas Pesona, CIMB Principal Equity Aggressive, Dana Ekuitas Prima, First State Dividend Yield, First State Indo Equity, Schroder Dana Prestasi, Schroder Dana Istimewa and TRIMKapital.